Geography of Food and the Urban Network in the Tri-Border Brazil-Peru-Colombia: The Case of Production and Commercialization of Poultry in the Amazon (2017)
In the Brazilian Amazon, a strong transformation of eating habits has been identified. An important element of this transformation is the replacement of locally obtained protein by “frozen” chicken meat. This transformation of eating habits occurs differently depending on the market structure, production and commerce. We sought to analyze the Tri-Border region of Brazil-Colombia-Peru from the perspective of the production and trade ofchicken. We identified the importance of the city of Tabatinga and the particularities of the other cities, as well as urban interactions, supply flows and the economic relations that occur with the nearby Peruvian and Colombian cities. Using “chicken” as an important variable, this paper discusses the urban network and the frontier dynamics in the western border of the Amazon.